2018
DOI: 10.1002/jcb.26788
|View full text |Cite
|
Sign up to set email alerts
|

SB‐216763, a GSK‐3β inhibitor, protects against aldosterone‐induced cardiac, and renal injury by activating autophagy

Abstract: Cardiovascular and renal inflammation induced by Aldosterone (Aldo) plays a pivotal role in the pathogenesis of hypertension and renal fibrosis. GSK‐3β contributes to inflammatory cardiovascular and renal diseases, but its role in Aldo‐induced hypertension, and renal damage is not clear. In the present study, rats were treated with Aldo combined with SB‐216763 (a GSK‐3β inhibitor) for 4 weeks. Hemodynamic, cardiac, and renal parameters were assayed at the indicated time. Here we found that rats treated with Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Activation of GSK3 by aldosterone has been recently reported in several studies (22)(23)(24). F7 Figure 7 shows that inhibition of GSK3 by two structurally unrelated pharmacological inhibitors SB216763 (Fig.…”
Section: Inhibition Of Aldosterone-activated Protein Kinase Activity ...mentioning
confidence: 70%
“…Activation of GSK3 by aldosterone has been recently reported in several studies (22)(23)(24). F7 Figure 7 shows that inhibition of GSK3 by two structurally unrelated pharmacological inhibitors SB216763 (Fig.…”
Section: Inhibition Of Aldosterone-activated Protein Kinase Activity ...mentioning
confidence: 70%
“…Numerous studies have shown that GSK-3β activation plays a wide spectrum of important roles in tissue fibrosis (Zhuang et al, 2018;Zeng et al, 2019). SB-216763, a GSK-3β inhibitor, protects against Aldo-induced renal injury by activating autophagy and might be a therapeutic option for renal fibrosis (Zhang et al, 2018b). Substrate competitive inhibitors (SCIs), a novel small molecule GSK-3 inhibitor, is considered to be highly selective and more suitable for clinical practice (Rippin et al, 2020).…”
Section: Exogenous Wnt Inhibitorsmentioning
confidence: 99%
“…GSK-3β inhibition by SB-216763 protected against aldosterone-induced renal and cardiac injuries by activating autophagy. 96 However, for cholestatic liver disease in a mouse model, a study by Zhuang et al . 97 demonstrated that SB-216763 therapy aggravated liver fibrosis.…”
Section: Therapeutic Solutionsmentioning
confidence: 99%